Vegetation analysis of lower Montane rainforest in Mt. Mandalagan, Negros Occidental - Cordon, Apollo B. (Animo Repository, 2003)
Vegetation analysis of lower montane rainforest (+-1200 masl) is conducted in North Negros Forest Reserve using belt-transect method. Five hundred eighty-two trees representing 49 species in 42 genera belonging to 34 families were found occurring in a one hectare inventory plot in the lower montane zone of Mt. Mandalagan. Of these, 24 or 48.98 percent were endemic to the Philippines. The combined basal area is measured at 27.588 m2ha-1 with an average dbh of 20.47 cm. With an average height of 8.31 m, this forest zone is formed by two-layer stratified forest canophy. Cyathea contaminans is the species with the highest importance value index having the most number of stems occurring in almost all subplots. Diospyros sp., Madhuca sp., and Ficus irisana were the next 3 important species. The family with the highest IVI was Moraceae, represented by 5 species. This family is noted for its relatively high measures for basal, density and frequency. Shannon index is calculated at 3.413, equitability or evenness index at 0.877, and Simpson index at 0.049. These measures indicate that species diversity in the study site is due to the presence of occasional species. The variance-to-mean ratio showed that the tree community follows a clumped disctribution. Two distinct tree communities were recognized in the study site based on structure and floristic composition using TWINSPAN and Ward's method of cluster analysis. These are the Madhuca-Platea-Garcinia (Group A) and the Cyathea-Diospyros-Weinmania (Group B) vegetation units. Groups A occurs at elevations from 1119-1172 masl, at relatively low slopes and is dominated by trees of Madhuca sp., Platea excelsa var. borneensis, and Garcinia sp. Group B occurs at elevations from 1142-1239 masl with relatively steep slopes. This is solely dominated by the tree fern Cyathea contaminans. Indirect gradient analysis (DCA) and direct gradient analysis (CCA) characterized the TWINSPAN delineated communities in terms of soil and environmental parameters. Steep slopes,